The Fusion of T2 Weighted MRI and Diffusion-Weighted Imaging in Evaluating the Depth of Myometrial Invasion in Endometrial Cancer - Ola Magdy Mohamed Shatat; Sherihan Fakhry; Maha Hussein Helal (Erciyes Medical Journal, 2019)
Objective: To investigate the performance of fused T2WI-diffusion-weighted imaging (DWI) in the preoperative evaluation of the depth of myometrial invasion in endometrial cancer. Materials and Methods: Twenty-nine patients with histologically proven endometrial carcinoma were enrolled in this study. All of them underwent a full magnetic resonance imaging exam including T2-weighted images and DWI with b values of 0, 500, and 1000 s/mm2. The ADC value in endometrial cancer and normal endometrium of control cases was calculated. The myometrial invasion depth was judged in each sequence separately as well as by fused images, and was correlated with the surgical pathology results. Results: In the evaluation of superficial myometrial invading lesions using the fused T2WI-DWI, the sensitivity was found to be 94.7%, specificity was 90%, and accuracy was 94.7%, while the values of about 90% sensitivity, 94.9% specificity, and 90% accuracy of fused T2WI-DWI in the evaluation of deep myometrial invading lesions were obtained. On the ADC maps, the mean ADC value of endometrial cancer was 0.9+-0.17×10−3 mm2/s and the mean ADC value of normal endometrium of control cases was 1+-0.11×10−3 mm2/s. Conclusion: The fusion of T2WI and DWI showed a good noninvasive diagnostic method of staging of invasion and preoperative depth. It can be used as an alternative diagnostic tool for endometrial carcinoma staging with reduced cost and injection of a contrast agent.